2022
DOI: 10.1021/acsaem.2c00734
|View full text |Cite
|
Sign up to set email alerts
|

Improved Interfacial Ion Transport through Nanofluidic Hybrid Membranes Based on Covalent Organic Frameworks for Osmotic Energy Generation

Abstract: Nanofluidic hybrid membranes integrated with asymmetrical surface charge, chemical composition, and geometric configuration exhibit unprecedented advantages in capturing the osmotic energy between river water and seawater. However, the output power is very restricted by the inefficient interfacial ion transport of the permselective membranes caused by the low-density pores and mismatch of the pore alignment. In this work, we developed a nanofluidic hybrid membrane constructed by ultrahigh pore-density covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Covalent organic frameworks (COFs), constructed from organic linkers, possess intrinsic structures and customizable organic linkers, which confer COFs with low density, large surface area, tunable pore size and structure, as well as easily modifiable functionality [55] . These properties attract increasing interests in different fields including osmotic energy conversion [26,56–63] . Kuo et al [56] .…”
Section: Various Materials For Osmotic Energy Conversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Covalent organic frameworks (COFs), constructed from organic linkers, possess intrinsic structures and customizable organic linkers, which confer COFs with low density, large surface area, tunable pore size and structure, as well as easily modifiable functionality [55] . These properties attract increasing interests in different fields including osmotic energy conversion [26,56–63] . Kuo et al [56] .…”
Section: Various Materials For Osmotic Energy Conversionmentioning
confidence: 99%
“…The presence of functional groups within these nanopores offers a promising avenue to achieve both high ion selectivity and permeability for osmotic energy harvesting, owing to the enhanced electrostatic interaction between ions and porous frameworks [64] . Furthermore, these functionalizable nanospaces can be intelligently regulated to control ion selectivity [57] . However, despite significant progress made in controlling MOFs membranes using certain methods, regulating dense MOFs membranes with charged functional groups remains challenging [64] .…”
Section: Various Materials For Osmotic Energy Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COF-LZU1 is prepared from a reaction between 1,3,5-Benzenetricarboxaldehyde and 1,4-diaminobenzene. A 4.26 Wm −2 maximum power density is obtained from a 50-fold salinity gradient of NaCl using the hybrid membrane [ 114 ].…”
Section: Emerging Porous Membranesmentioning
confidence: 99%
“…Recently, hybrid membranes of COF‐LZU1 and carbon nanotube/cellulose nanofiber were found to increase interfacial ion transport efficiency and possess diode behavior, which was attributed to the asymmetrical geometry configuration and charge distribution under a high pH condition. [ 30 ] After the submission of the current study, an ionic diode COF membrane was reported by comprising two oppositely charged COFs (TpPa‐SO 3 Na and TpEB) and demonstrated efficient osmotic energy conversion. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%